The stress-strain behaviour of soils containing gas bubbles - Wheeler, S; S. J. Wheeler (1986)
The stress-strain behaviour of unsaturated soils containing discrete bubbles of gas has been studied in a programme of experimental and theoretical research. The research is of particular relevance to the offshore environment, where bubbles of methane, nitrogen and carbon dioxide are formed within the seabed by the decomposition of organic matter. The presence of these gas bubbles can have a major influence on the engineering properties of the soil. As gas bubbles in marine sediments are typically much larger than the normal void spaces, the bubbles cannot be considered as simply changing the compressibility of the pore fluid. Chapters 2 to 4 describe a series of undrained triaxial tests on reconstituted samples of clayey silt from an estuarine site. Bubbles of methane were formed within the soil by using a chemical technique. The test results provide evidence of the effect of gas bubbles on the undrained shear strength, together with useful information on the stress-strain behaviour prior to failure, the generation of pore pressures during shearing, the elastic moduli and the isotropic consolidation behaviour. A theoretical model for soils containing large gas bubbles is developed in Chapter 5. The model consists of spherical bubble cavities surrounded by a matrix of saturated soil. In the following three chapters various aspects of the soil behaviour are examined by analysing the theoretical model. Chapter 6 covers the elastic moduli, Chapter 7 the consolidation behaviour and Chapter 8 the undrained shear strength. In Chapter 9 the predictions of the theoretical model are compared with the experimental results. The agreement between theory and experiment is excellent, suggesting that the theoretical approach developed and analysed in Chapters 5 to 8 is a reasonable model for the behaviour of soils containing large gas bubbles.